Urgensi Reaktualisasi Undang-Undang Nomor 28 Tahun 2014 Untuk Menjawab Tantangan Perlindungan Hak Cipta Digital - Habibi, Muhammad; Annisa, Ajeng Nur; Husni, Ali (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Digital transformation presents new challenges for copyright protection in Indonesia. Law No. 28 of 2014 on Copyright is considered to be insufficiently responsive to the dynamics of digital infringement, such as illegal distribution, works based on modern technology, and weaknesses in the protection system and royalty distribution on digital platforms. This article discusses the urgency of updating the Copyright Law to make it more adaptive, including expanding the scope of protection in the digital realm, integrating security technologies such as Digital Rights Management (DRM) and watermarking, strengthening the responsibility of User-Generated Content (UGC) platforms, and aligning regulations with international standards. Key challenges include the difficulty of cross-border law enforcement, low public literacy, dualism in protection systems, and the lack of transparency in collective management organizations. Proposed solutions include inter-agency collaboration, improving public literacy, utilizing work protection technologies, and reforming the royalty distribution system. With comprehensive regulatory updates and cross-sector collaboration, copyright protection in Indonesia is expected to become more effective and competitive in the digital age.